Weedy Rice as a Novel Gene Resource: A Genome-Wide Association Study of Anthocyanin Biosynthesis and an Evaluation of Nutritional Quality - Wang, Wenjia; Zhao, Minghui; Zhang, Guangchen; Liu, Zimeng; Hua, Yuchen; Jia, Xingtian; Song, Jiayu; Ma, Dianrong; Sun, Jian (Frontiers in Plant Science, 2020)
The pericarp color of rice grains is an important agronomic trait affected by domestication, and the color pigment, anthocyanin, is one of the key determinants of rice nutritional quality. Weedy rice, also called red rice because its pericarp is often red, may be a novel gene resource for the development of new rice. However, the genetic basis and nutritional quality of anthocyanin are poorly known. In this study, we used a genome-wide association study (GWAS) to find novel and specific QTLs of red pericarp in weedy rice. The known key gene site of red pericarp Rc was detected as the common genetic basis of both weedy and cultivated rice, and another 13 associated signals of pericarp color that were identified may contribute specifically to weedy rice pericarp color. We then nominated three pericarp color genes that may contribute to weedy rice divergence from cultivated rice based on selection sweep analysis. After clarifying the distribution and growth dynamics of pigment in weedy rice caryopsis, we compared its nutritional quality with cultivated rice. We found that sampled weedy rice pericarps had much greater quantities of anthocyanin, beneficial trace elements, free amino acids, and unsaturated fatty acids than the cultivated rice. In conclusion, the gene resources and novel genetic systems of rice anthocyanin biosynthesis explored in this study are of great value for the development of nutritious, high anthocyanin content rice.